The frequency of adenotonsillectomies in relation to socioeconomic status among primary school students in Yozgat province - Ozkırış, Mahmut; Kapusuz, Zeliha; Saydam, Levent (The Turkish Journal of Pediatrics, 2013)
The present study aimed to investigate the frequency of tonsillectomy and adenoidectomy and its relation to socioeconomic status (SES) among 6- to 13-year-old primary school students in Yozgat province. Between March 1, 2012 and March 15, 2012, 1098 primary and nursery school students who had complete ear, nose and throat examination in our department were included in the study. The students were queried regarding age, gender and history of tonsillectomy and adenoidectomy via data collection forms. SES was evaluated according to the mean monthly income within the family, educational level of parents and absence or presence of smoking habits. The age of the 1098 students (678 males, 420 females) ranged between 6 and 13 years (mean age: 10.7). Of the cases, 27 (2.5%) had tonsillectomy, 23 (2.1%) had adenoidectomy, and 36 (3.3%) had both tonsillectomy and adenoidectomy. When we compared the SES between the operated and nonoperated subjects in the families with mean monthly income lower than the minimum wage, educational level lower than university degree and in the presence of smoking habits, adenotonsillectomy operation rate was significantly higher than in the non-operated group (p